2006
DOI: 10.1523/jneurosci.2014-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Area Postrema Neurons Are Modulated by the Adipocyte Hormone Adiponectin

Abstract: Adiponectin is an adipocyte-derived peptide hormone involved in energy homeostasis and the pathogenesis of obesity, including hypertension. Area postrema (AP) lacks a blood-brain barrier and is a critical homeostatic integration center for humoral and neural signals. Here we investigate the role of AP in adiponectin signaling. We show that rat AP expresses AdipoR1 and AdipoR2 adiponectin receptor mRNA. We used current-clamp electrophysiology to investigate whether adiponectin influenced membrane properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
1
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 53 publications
(58 reference statements)
2
69
1
9
Order By: Relevance
“…All animal protocols conformed to the standards of the Canadian Council on Animal Care and the Queen's University Animal Care Committee. Cell cultures were prepared according to protocols modified from Fry et al (20) and Brewer (6). Briefly, three or four Sprague-Dawley (ϳ150 g) rats were decapitated, and the brains were quickly removed and placed into oxygenated, ice-cold artificial cerebral-spinal fluid containing the following (in mM): 124 NaCl, 2 KCl, 1.25 KH 2PO4, 2.0 CaCl2, 1.3 MgSO4, 20 NaHCO3, and 10 glucose.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All animal protocols conformed to the standards of the Canadian Council on Animal Care and the Queen's University Animal Care Committee. Cell cultures were prepared according to protocols modified from Fry et al (20) and Brewer (6). Briefly, three or four Sprague-Dawley (ϳ150 g) rats were decapitated, and the brains were quickly removed and placed into oxygenated, ice-cold artificial cerebral-spinal fluid containing the following (in mM): 124 NaCl, 2 KCl, 1.25 KH 2PO4, 2.0 CaCl2, 1.3 MgSO4, 20 NaHCO3, and 10 glucose.…”
Section: Methodsmentioning
confidence: 99%
“…Responsiveness of AP neurons to 1 M-1 pM ghrelin was determined by comparing membrane potential of neurons before and after direct application. AP neurons were considered responsive if their mean membrane potential demonstrated a shift of at least 4.5 mV or a change in firing frequency of greater than 1 Hz (over a 60-s period) during the 120 s after application compared with the 100 s before application (20). Outward K ϩ currents were elicited by step depolarizations from a holding potential of Ϫ100 mV.…”
Section: Methodsmentioning
confidence: 99%
“…Although previous studies have indicated the presence of AdipoR1 and AdipoR2 in the brain (16,20,21), the distribution of these receptors in discrete brain areas implicated in mood regulation remain unclear. In situ hybridization with specific cRNA probes revealed that AdipoR1 mRNA was highly expressed in various brain regions, such as the medial prefrontal cortex (mPFC), hippocampus, and amygdala (Fig.…”
Section: Adiponectin Haploinsufficiency Impairs Glucocorticoid-mediatedmentioning
confidence: 97%
“…injection (16). Previous studies have demonstrated the presence of adiponectin receptors, AdipoR1 and AdipoR2, in the central nervous system (16,(18)(19)(20)(21); however, their expression patterns in discrete brain areas remain to be determined.…”
mentioning
confidence: 99%
“…Cells in the AP were either hyperpolarized or depolarized by adiponectin, thus proving a possible mechanism for the central regulation of cardiovascular function (98).…”
Section: Note Added In Proofmentioning
confidence: 99%